The Correlation between Locus of Control and Social Support on Student’s Career Adaptability - Safitri, Indah; Eddy Wibowo, Mungin; Sunawan, sunawan (Jurnal Bimbingan Konseling, 2021)
Students who have good career adaptability tend to have self-understanding regarding interest, talent, and passion they have. This research aimed to determine the correlation between internal locus of control and social support on career adaptability of the Public Senior High School students in Pemalang Regency. In collecting the data, the researchers used the scales of internal locus of control, social support, and career adaptability. In addition, cluster random sampling technique was used to sample the total of 10,034 students into 346 students. Their data were analyzed using hierarchical regression analysis with the help of SPSS version 25.0 software. Findings showed that partially internal locus of control had a positive and significant relationship with career adaptability, while external locus of control did not. Further, social support partially had a positive and significant relationship with career adaptability. Of the social support components, the only one which could predict students’ career adaptability was family. Meanwhile, the external locus of control group showed no relationship with social support on career adaptability. This explanation confirms that social support from family has an important role for students who have internal locus of control to improve career adaptability.